Tata Cara Pelaksanaan Ishlah Dalam Pembagian Waris Perspektif Kompilasi Hukum Islam - Dzin Nun Naachy; Hanik Latifah (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2022)
Background. The Compilation of Islamic Law in determining the law allows the implementation of the distribution of inheritance in a peaceful manner agreed upon by the family without following the procedures for the distribution of inheritance with the share specified in Islamic law.Aim. This study aims to discusses the procedure for distributing inheritance in a peaceful manner which is most relevant from the perspective of the Compilation of Islamic Law.Methods. This literature research uses the jurisprudence law approach. The research data were taken from the Qur'an and the Compilation of Islamic Law Articles 171-182 and Article 210 as primary data sources.Results. The results of the study show that the implementation of peace in the distribution of inheritance can use the Takharruj method and the Hibah method. The procedure for dividing inheritance by grants is more appropriate in the perspective of the Compilation of Islamic Law.